Clathria (Thalysias) (Poecilosclerida: Demospongiae: Porifera) from Brazil: New species and redescription of Clathria (Thalysias) basiarenacea (Boury-Esnault, 1973) - Galindo, Helcy; Hooper, John N.a.; Pinheiro, Ulisses (Zootaxa, 2014)
The subgenus Clathria (Thalysias) Duchassaing & Michelotti, 1864 has 97 valid species, of which 27 are recorded in the Atlantic Ocean. However, only three species are known from Brazil so far. Here we provide the redescription of Clathria (Thalysias) basiarenacea (Boury- Esnault, 1973), based on the discovery of new characters (additional category of auxiliary styles, and details of spicules), and describe a new species of Clathria (Thalysias) repens sp. nov., that differs from sister species in having a live orange color, a massively encrusting repent growth form with lamellate folds and anastomosed projections, and three categories of structural styles, of which the two auxiliary styles have microspined heads. We also invalidate the record of Clathria (Thalysias) procera (Ridley, 1884) for Brazil.